Overcoming the Educational Resource Equity Gap: A Close Look at Distributing a School’s Financial and Human Resources - Coffin, Stephen V. (Rowman & Littlefield Publishers, 2023)
State school finance formula cause funding inadequacy, allocative inefficiency, and educational resource equity gaps. Legislative and court-ordered remedies have failed to solve the disparities among schools and districts. This book’s ground-breaking innovation shows how toshift the public education finance paradigm to fund K-12 public education properly, fully, and equitably by eliminating the duplicative and unnecessary layer of county government nationwide and repurposing those tax dollars while implementing economies of scale to achieve allocative efficiency.